Geology, structure and lithostratigraphic framework of the Rakhine Coastal Ranges in western Myanmar: Implications for the collision of the India Plate and West Myanmar Block. (1st July 2020) - Khin, Kyi; Moe, Aung; Myint, Myo
Graphical abstract: Abstract: Termination of the eastward subduction of the Indian Plate is inferred to be latest Eocene in age in the north-easternmost Assam and Myanmar regions, followed by the collision of the Indian continent with the Asia Plate. This event is typically represented by the underthrusting of the Middle and Upper Eocene Sylhet Formation, which was deposited on the western margin of India Plate, beneath the Eocene Disang Formation, while the northern margin of India collided against Eurasia and Tibet along a zone, which lies south of the Triassic-Jurassic deep-marine sediments and Yarlung ophiolite in the latest Eocene. Later movement of the Naga and Disang Thrusts to the east suggests convergence between the Burma and Indian Plates, as both moved northwards and India rotated anti-clockwise after the collision. The stratigraphic records indicate that an early Oligocene emplacement of the deep-marine sedimentary sequence on the India plate, probably within 10 Ma interval age during the India-Asia collision, and moved northwards. Oblique convergence could also have resulted from possible clockwise rotation of SE Asia relative to the Indian Plate accompanying the eastward translation of South China along strike-slip faults. The deformation of western and southern Myanmar is still active today with under-thrusting related to subduction. The basement of the Indian Plate below the Indo-Myanmar Ranges is moving towards the north with respect to the rest of Asia. This study provides the syn- and post-deformation history of Neogene siliciclastic sequences of the Rakhine Coastal Ranges in western Myanmar allowing structural and kinematic interpretation of the oblique subduction and collision history. The growth of these folds and faults and associated uplift were resulted from the tectonic processes and evolution in which the Burma Plate was wedged in the subduction zone and dragged towards the north with the Indian Plate between internal N-S trending right-lateral shearing and external E-W shortening.